Political Life in Society 5.0: Implications of Justice and Equality - Damayanti, Cicilia (International Journal of Indonesian Philosophy & Theology, 2024)
Technology has expanded access to information and made political participation easier for people. However, technology also has the potential to exacerbate political problems, depending on how it is used and regulated. Solutions to political and technological problems depend on actions taken by governments, the technology industry, and society, including the wise use of technology and ensuring it does not harm human rights. Everyone should be a continuous learner, a wise user, and advocate for digital rights and participation in technology politics. Inclusion, transparency, and responsibility should be the foundation of technology politics, so that technology can help address various political and social issues today. However, the use of technology must be based on inclusive, fair, and responsible principles, and consider its impact on society and the environment. This research was conducted using the method of book analysis from several authors who wrote about politics and Society 5.0. This paper also provides an overview of what Society 5.0 is, how it differs from previous eras, and how it affects politics and society. Technology can be a solution for current political development, but only if used wisely and supported by appropriate policies and regulations.